Project-Based Learning in Teaching Diode Bias Characteristics to Vocational Students - Athaya, Ratu; Fathimatuzzahro, Fathimatuzzahro; Afrian, Afrian; Fitria, Zahira Adimaya; Fitriani, Rayanti Nur (MJI Publisher, 2025)
Comprehending diode bias characteristics is an essential skill for vocational students in electronics, serving as a foundation for understanding more intricate circuit behaviors. This article outlines the creation and execution of a Project-Based Learning (PBL) model designed to assist students in comprehending the idea of diode bias, encompassing both forward and reverse bias operations. The instructional design was created to promote active learning via project activities, including the assembly of basic diode circuits, observation of their behavior, and presentation of results. The PBL framework was organized into distinct stages: problem identification, planning, prototyping, testing, and reflection. This approach seeks to enhance students' conceptual comprehension and practical application of semiconductor principles through the integration of real-world tasks and collaborative learning. The development process encompasses instructional materials like worksheets, circuit kits, and reflection notebooks. This article enhances vocational learning methodologies by offering a contextual, practical method for teaching abstract electronic topics.